PEDAGOGICAL-PSYCHOLOGICAL CONDITIONS ENSURING THE DEVELOPMENT OF COGNITIVE COMPETENCE OF FUTURE INFORMATICS TEACHERS - Bozorova O'g'iloy Hikmat kizi (Bright Mind Publishing, 2026)
This article analyzes the pedagogical and psychological conditions that ensure the development of cognitive competence in future informatics teachers under the conditions of digital transformation. Based on the normative-legal documents of the Republic of Uzbekistan in the field of education — in particular, the “Concept for the Development of the Public Education System until 2030” and the “State Educational Standard of General Secondary Education” — the content of cognitive competence and methodological directions for its formation are discussed. The article examines the interrelation between the digital learning environment, the teacher’s digital and pedagogical competence, students’ intellectual potential, socio-cultural factors, and the influence of information and communication technologies on the educational process. The role of the subject “Informatics and Information Technologies” in developing students’ cognitive competence is substantiated, and conclusions and recommendations are presented regarding the pedagogical and psychological conditions necessary for the preparation of future informatics teachers.
Keywords: Cognitive competence, intellectual potential, digital learning environment, future informatics teacher, information and communication technologies, pedagogical and psychological conditions, state educational standard.